Safety and Efficacy of Immune Checkpoint Inhibitors for Patients With Metastatic Urothelial Carcinoma and End-Stage Renal Disease: Experiences From Real-World Practice - Kuo, Ming-Chun; Su, Po-Jung; Huang, Chun-Chieh; Luo, Hao-Lun; Chiu, Tai-Jan; Li, Shau-Hsuan; Wu, Chia-Che; Liu, Ting-Ting; Cheng, Yuan-Tso; Kang, Chih-Hsiung; Su, Yu-Li (Frontiers in Oncology, 2020)
Background Immune checkpoint inhibitors (ICIs) are used widely for treating metastatic urothelial carcinoma (mUC). In practical settings, evidence is lacking on the efficacy of ICIs in some difficult-to-treat patients, such as those with end-stage renal disease (ESRD). Herein, we evaluate the safety and efficacy of ICIs for patients with mUC and ESRD. Methods For this retrospective study, patients with mUC who were given ICIs at Kaohsiung Chang Gang Memorial Hospital and Linkou Chang Gung Memorial Hospital between April 2016 and November 2019 were consecutively enrolled. All clinicopathologic data, treatment responses, and adverse events were recorded. The immune-related adverse events (AEs), objective response rate (ORR), progression-free survival (PFS), and overall survival (OS) were compared between ESRD and non-ESRD groups. Results In total, 129 patients with mUC were enrolled, with 11 patients categorized as the ESRD group. Among these patients with ESRD receiving ICIs, 7 of 11 (63.6%) had high-grade (grade ≥3) AEs, chiefly hematologic toxicity. Some rarely encountered AEs were noted, including toxic epidermal necrolysis, tuberculosis reactivation, ascites, and cytokine release syndrome. Patients in the ESRD group had numerically higher ORR (54.5% vs. 28.8%, p = 0.09), PFS (7.1 vs. 3.5 months, p = 0.42), and OS (not reached vs. 15.4 months) than the non-ESRD group. A multivariate Cox regression model demonstrated that leukocytosis (hazard ratio [HR]: 2.63; 95% confidence interval [CI]: 1.23–5.63; p = 0.01) and neutrophil-to-lymphocyte ratio (HR 2.91; 95% CI: 1.30–6.53; p = 0.01) were independent prognostic factors. Conclusion Administration of ICIs in patients with mUC and ESRD demonstrated a modest antitumor activity, and should be used with caution for increasing risk of hematologic toxicity.